Yaşlanmanın Coğrafyaları: Coğrafi Gerontolojide İlerleme, Tartışmalar ve Araştırma Gündemi - Ertuğrul Murat Özgür (Coğrafi Bilimler Dergisi, 2019)
Geography is one of the many disciplines actively involved in studies conducted in the developing world. The role of geographical research in social gerontology was first described when the studies conducted in early 1970's showed that elders presented themselves in a certain environment in relation to the aging process, that they experienced and used those environment and thus understanding that the aging process of the environment was affected by it, because the synthesizing and holistic tradition of geography represents an effective methodology to evaluate the complex interaction between elders and their environment. A new discipline, called geographical gerontology, positioned at an intersection between geography and gerontology, has been developing structurally in institutions of the western world and intellectually, both in the academic debates of disciplines and in key empirical research areas. This study aims to grab attention of human geographers by handling the aging population issue that has taken its place in political and academic agenda of Turkey in last decades from the geography of aging perspective and to introduce a newly emerging and rapidly developing discipline and point to its main research areas in this context.